Assessment of the thorax is equivalent when presented with whole body versus collimated thoracic radiographs in dogs and cats. - Kurihara, Manabu.; Solano, Mauricio.; Motegi, Tomoki. (Tufts University. Tisch Library., 2025)
Keywords: Radiography, Digital radiography, Collimation, Radiographic techniques.; Springer Open.